1992
DOI: 10.1002/j.1556-6676.1992.tb02147.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pursuit of Quality: A Look Into the Future of CACREP

Abstract: This is a look into the future of the Council for Accreditation of Counseling and Related Educational Programs (CACREP). A brief review summarizes the context in which it will find itself in the next decade. Two primary issues that must be addressed should serve as the basis for changes. First, what are the societal needs that counselors will be required to address? Second, what preparation is appropriate for counselors to meet these needs? Suggested changes with supporting rationale are discussed for the prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Several articles published over the past 20 years have recounted the history of CACREP (Haight. 1992;Smaby & D'Andrea, 1995;Sweeney.…”
Section: Perspectives On Cacrepmentioning
confidence: 99%
“…Several articles published over the past 20 years have recounted the history of CACREP (Haight. 1992;Smaby & D'Andrea, 1995;Sweeney.…”
Section: Perspectives On Cacrepmentioning
confidence: 99%
“…Among these perceived benefits were increased internship and job opportunities, improved student quality, helpfulness in private practice, increased faculty professional involvement and publishing, and acceptance into a counselor education doctoral program. There is little research comparing the performance of CACREP‐accredited and non‐CACREP‐accredited graduates (Haight, 1992; Schmidt, 1999). One large study using NCE data showed that students from CACREP‐accredited programs performed significantly better on the NCE than did students from non‐CACREP‐accredited programs (Adams, 2006).…”
Section: Cacrep Accreditationmentioning
confidence: 99%
“…CACREP accreditation has proven beneficial to programs that have sought it (Haight, 1992) and, according to Vacc (1 992), both CACREP-accredited and non-CACREPaccredited programs value CACREP accreditation. One study found that 79% of the CACREP-accredited programs surveyed believed that the investment of time, money, and energy in seeking accreditation was worthwhile (Cecil & Comas, 1986).…”
Section: Benefitsmentioning
confidence: 99%